2017
DOI: 10.3390/en10040533
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Silicon Carbide Devices on the Powertrain Systems in Electric Vehicles

Abstract: Abstract:The DC/DC converters and DC/AC inverters based on silicon carbide (SiC) devices as battery interfaces, motor drives, etc., in electric vehicles (EVs) benefit from their low resistances, fast switching speed, high temperature tolerance, etc. Such advantages could improve the power density and efficiency of the converter and inverter systems in EVs. Furthermore, the total powertrain system in EVs is also affected by the converter and inverter system based on SiC, especially the capacity of the battery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The second stage for the control development began with the search of the switching frequency for each converter. For doing the search, a random frequency (fs) was assigned, and with this frequency, three conditions for the analysis were established by (8):…”
Section: Proposed Methods Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second stage for the control development began with the search of the switching frequency for each converter. For doing the search, a random frequency (fs) was assigned, and with this frequency, three conditions for the analysis were established by (8):…”
Section: Proposed Methods Descriptionmentioning
confidence: 99%
“…Recent research has shown the advantages and disadvantages of the SiC devices. These elements possess better characteristics than silicon devices, such as low switching losses, higher switching frequencies, and higher temperature operation ranges [4][5][6][7][8]. Accordingly, the SiC devices allow for the design of power converters with high-power densities and high efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing storage system innovations, the supercapacitor significantly increased their performance in terms of energy density [19,20], so that their use become possible with a proper sizing; indeed many studies focused on the combined use of supercapacitors and batteries as storage system in hybrid vehicle applications [21][22][23][24][25]. In addition to that, the availability of low-loss power electronics devices, such as Silicon Carbide (SiC) metal-oxide-semiconductor field-effect transistor (MOSFET) [26,27], allows to design high efficiency power converter. Storage systems and power converters efficiency highly influence series architecture fuel consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, motor drives supplied by a SiC based voltage source inverter (VSI) can provide lower losses, higher efficiency, and a smaller size when compared with their silicon (Si) counterparts [1,2]. All these features contribute to these devices generating interest in applications for electric traction systems, where a long life time is important, and by reducing the losses in such applications, the life time can be extended [3,4]. high switching speed, i.e., high overvoltages.…”
Section: Introductionmentioning
confidence: 99%